Exploring the antimicrobial and antituberculosis potential of diorganotin(IV) complexes derived from hydrazone ligands: Synthesis and their structural elucidation - Poonia, Shikha (RSYN Proceedings, 2025)
In our present work, we have synthesized four diorganotin(IV) complexes (R2SnL where, R = methyl, ethyl, butyl and phenyl groups) from hydrazone ligand, which was derived from 4-nitro-3-methoxybenzhydrazide and benzaldehyde derivatives. Hydrazones are classified as "privileged ligands" due to their ability to readily bind with metal ions. They exhibit exceptional affinity for complexation owing to their favourable solubility, robust stability, facile synthesis, and the presence of the (–NH–C=O) group in close proximity to the azomethine group, rendering them effective chelating agents. Organotin(IV) complexes incorporating hydrazone components hold significant relevance in the pharmaceutical industry. All the prepared compounds were characterized with the help of numerous spectroscopic techniques like FT-IR, (1H, 13C & 119Sn) NMR, and Mass spectrometry. Spectroscopic analysis indicated a penta-coordinated configuration around the tin metal atom, with the ligand binding to the tin atom in a tridentate manner through enolic O, imine N, and phenolic O donor atoms. Furthermore, the synthesised compounds have been analysed for theirinvitroantituberculosis and antimicrobial efficacyand the results were compared with values of standard drugs. The findings illustrated that diorganotin(IV) complexes exhibited superior activity as compared to their parent ligand. The results depicted that compound [Ph2SnL] with MIC = 0.0195 ± 0.0048 μmol/mL value showed greater potential against E. coliand C. albicans strains.